Firestorm - Robson, Mark, 1966- (London : Simon and Schuster, 2008)
Nolita, terrified of dragons, must overcome her fears to learn to fly her day dragon and find the first of four Orbs, which combined can save the leader of all dragon kind.
7.4
3-6
3-6
Keywords: Dragons -- Juvenile fiction; Dragons -- Fiction; Fantasy; Dragons -- Fiction; Fantastic fiction; Fantastic fiction